Distinct distribution and responses of IgM+, IgT1+ and IgT2+ B cells in common carp - Eltijani, Awatif; Embregts, Carmen W. E.; Magadan, Susana; Wang, Jingjing; Brugman, Sylvia; Boudinot, Pierre; Wiegertjes, Geert F.; Forlenza, Maria (Frontiers in Immunology, 2024)
In teleosts, the immunoglobulin classes produced by B cells are IgM, IgD, and IgT/IgZ. IgT was initially described as an immunoglobulin specialized in mucosal responses; accumulating evidence, however, shows that it is also involved in systemic immune responses. Two types of IgT/IgZ (IgT1 and IgT2) were previously described in common carp, but their further characterization was hampered by the lack of specific tool. In the current study, we developed and validated polyclonal antibodies against carp IgT1 and IgT2 and used them in combination with well validated monoclonal antibody against carp IgM (WCI12), to study the distribution of IgM+, IgT1+ and IgT2+ B cells or their secreted immunoglobulins in various mucosal and systemic organs of carp. Finally, we also preliminary assessed the B cell response to infection with the blood-borne parasite Trypanoplasma borreli. Using these tools, we report on the distinct expression of soluble immunoglobulins in systemic and mucosal compartments. IgT1 and IgM were expressed in mucosal as well as systemic organs and responded to systemic parasitic infection, whereas IgT2 was preferentially expressed at mucosal sites and did not respond to systemic infections. By studying the distribution of B cells in different organs, compartmentalization of the three B cell subtypes was observed in gills and gut, whereas splenic B cells appeared as organized clusters around ellipsoids. Our results provide insights into the distribution and to some extent the function of B cells in carp, indicating that our newly developed tools are valuable for future studies aiming at the further characterization of immune responses of carp to infections and vaccination.